Combined multiplex polymerase chain reaction-based targeted next−generation sequencing and serum 1, 3-β-D-glucan for differential diagnosis of Pneumocystis pneumonia and Pneumocystis colonization - Wang, Hansheng; Chen, Xiao; Wu, Xiaofeng; Cao, Qizhen; Wu, Yi; Wang, Fang; Wang, Yunyun; Zhou, Yanhui; Tang, Yijun; Ren, Tao; Wang, Meifang (Frontiers in Cellular and Infection Microbiology, 2025)
Background and ObjectivePneumocystis jirovecii pneumonia (PjP) remains an important cause of morbimortality worldwide, and differentiating Pneumocystis jirovecii (P. jirovecii) infection from P. jirovecii colonization (PjC) is crucial for guiding treatment strategies. Multiplex polymerase chain reaction-based targeted next-generation sequencing (mp-tNGS) is a promising tool for identifying lower respiratory tract infections, with a detectable pathogen spectrum that covers more than 95% of clinical infectious cases. This study evaluated mp-tNGS for P. jirovecii identification in bronchoalveolar lavage fluid (BALF) samples combined with serum 1,3-β-D-glucan (BDG) level detection to differentiate PjP and PjC.MethodsA total of 73 patients were enrolled and the final diagnosis was used as a reference criterion, and patients were divided into the PjP group and PjC group. The clinical data and detection performance of mp-tNGS/serum BDG were analyzed.ResultsThe median fungal reads (normalized sequence counts) detected by mp-tNGS were 1522.00 (interquartile range [IQR], 581.5, 4898.0) in the PjP group versus 117.00 (IQR, 79.00, 257.00) in the PjC group (p <0.0001). Correspondingly, BDG levels were 122.5 (88.75,239.3) pg/ml in PjP patients compared to 59.00 (51.0,79.0) pg/ml in PjC patients (p <0.0001). Area under the receiver operator characteristic curve (AUROC) for discriminating PjP from colonization was 0.935 (95% CI: 0.88–0.99) for BALF mp-tNGS and 0.822 (95% CI: 0.72–0.93) for serum BDG. The optimal diagnostic thresholds were determined to be 355 reads for mp-tNGS (sensitivity: 89.1%; specificity: 85.2%) and 84.5 pg/ml for BDG (sensitivity: 85.2%; specificity: 80.4%).ConclusionBALF mp-tNGS and serum BDG serve as valuable adjunct diagnostic tools, providing reliable differentiation between P. jirovecii colonization and active infection.